1996
DOI: 10.1128/aac.40.4.1053
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between rifampin MICs for and rpoB mutations of Mycobacterium tuberculosis strains isolated in Japan

Abstract: We analyzed the relationship between rifampin MICs and rpoB mutations of 40 clinical isolates of Mycobacterium tuberculosis. A point mutation in either codon 516, 526, or 531 was found in 13 strains requiring MICs of > or = 64 micrograms/ml, while 21 strains requiring MICs of < or = 1 microgram/ml showed no alteration in these codons. However, 3 of these 21 strains contained a point mutation in either codon 515 or 533. Of the other six strains requiring MICs between 2 and 32 micrograms/ml, three containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
58
4
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 25 publications
13
58
4
2
Order By: Relevance
“…The combination of mutations involving katG S315T mutation was 95.1% ( n = 442), and this mutation is described as having the association with higher levels of resistance to INH (MIC, ≥100 µg/ml). This data is consistent with earlier reports [21,3234]. …”
Section: Discussionsupporting
confidence: 94%
“…The combination of mutations involving katG S315T mutation was 95.1% ( n = 442), and this mutation is described as having the association with higher levels of resistance to INH (MIC, ≥100 µg/ml). This data is consistent with earlier reports [21,3234]. …”
Section: Discussionsupporting
confidence: 94%
“…9,13,22,26,36,37 Mutations of codon 531, 526, and 516 have been reported as the most frequent mutations in the mutation hotspot region of the rpoB gene of MTB worldwide. 3,23,36 In the present study, the majority of mutations occurred at codon 526, and the mutation frequency (48.4%) observed was slightly higher than frequencies reported by China (40%), 36 Japan (35%), 16 and Korea (38%). 9 However, the frequency of occurrence of the mutation at codon 526 in India, the closest neighbor to Sri Lanka, is much higher (93%) as reported by Sharma et al (2003).…”
Section: Discussioncontrasting
confidence: 78%
“…24 The frequency of mutation at codon 531 (9.7%) was comparatively low in MTB isolates from Sri Lanka in relation to mutation frequencies reported by other countries, including India (47%), 10 Australia (52%), 37 Vietnam (31%), 4 and Poland (41%). 23 However, the base change observed at codon 531 was a TCG to TTG (transition mutation) as commonly reported by several Asian countries ( Japan, 16 China, 36 Korea, 9 and India 11 ) and other countries such as Greece 12 and Italy. 18 Previous studies have reported that a mutation at codon 531 is frequently associated with the codon 526 mutation in certain regions of the world.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, a low degree of drug-resistance (MIC ≥ 12.5 μg/ml) is conferred by nucleotide substitutions in codons 514, 521, 533 [29]. Mutations in codon 516 are also associated with a high degree of resistance (MIC ≥ 64 μg/ml) [30, 31]. Although some studies report similar results, H526L and H526N mutations are the exception; in these cases, the MIC values did not exceed 8 and 16 μg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%